Contemporary cultures and their relationship to adolescent behavior (Korean culture) as a model - Zahra Hadi Kazem (Basrah Arts Journal, 2023)
Going into any aspect of adolescence is one of the important basics for evaluating society, this is due to the importance of this age stage that determines building the personality of a normal individual and establishing him in a positive way for his later life stages. Therefore, this study deals with the topic of contemporary cultures and their relationship to adolescent behavior (Korean culture). a model. And due to the development of contemporary lifestyles and the diversity of cultures that target the behavior of adolescents as the most effective category in determining the future and destiny of society, new concepts and intellectual diversity have emerged that begin to control the penetration of this age group’s thinking to target the culture of any society in general, and especially in affecting adolescents in some respects. Life, such as talents and ambition, such as (music, dance, movies), and it is one of the factors influencing the difference of cultures, and the introduction of certain social standards, whether in moral values, beliefs, politics, art, technologies, or marketing, an attempt to control the basis and thought of a society.